The Development of Si Mirasantika Android-Based Media with 4D Models in Classical Guidance Services - Subkan, Muhammad; Atiqoh, Atiqoh; Suhari, Suhari (EDUCATIO : Journal of Education, 2022)
The aim of this research is to develop the Si Mirasantika media as an information medium to raise awareness about drug abuse types and effects among students at SMK Negeri 1 Brondong Lamongan. This media aims to foster moral expertise, moral sentiments for preventing drug abuse, and moral actions in drug prevention within the context of Classical Guidance. The development of Si Mirasantika Android-based media involved a structured approach. The media's content is organized into three main parts: opening, contents, and closing, which encompass sections such as introduction to drugs, factors of drug abuse, and methods of cure. Feedback and revisions were conducted based on trial data analysis, addressing aspects including subject matter, auxiliary information, affective considerations, interface, navigation, pedagogy, and robustness. Evaluation was performed by expert media validators, media design experts, content/material experts, and target trials. The results indicate that the Si Mirasantika media is suitable for use by students at SMK Negeri 1 Brondong Lamongan, as validated by media experts, design experts, and content/material experts. The media received high validity scores, with the media design expert validation at 90.67%. Feasibility tests in small and medium classes showed positive outcomes, with effectiveness tests in the large class achieving a very effective score of 80.07%. These results support the utilization of Si Mirasantika as a supplementary resource in Classical Guidance, enhancing students' knowledge and understanding of drug abuse prevention.